The impact of obesity on the perception of self-concept in children and adolescents - Helio Serassuelo Junior; Timothy Gustavo Cavazzotto; Ana Carolina Paludo; Lidyane Ferreira Zambrin; Antônio Carlos Simões (Revista Brasileira de Cineantropometria e Desempenho Humano, 2015)
The objective of this study was to investigate the impact of overweight and obesity on the perception of self-concept in children and adolescents. A total of 785 schoolchildren, 410 girls (11.44 ± 1.84 years), participated in the study. The sample was divided into normal weight, overweight and obese groups according to the BMI criteria proposed by Cole et al. (2000). Socioeconomic status (SES) was evaluated according to the ABEP (2010) and self-concept was rated using the Piers-Harris 2 Scale. The results showed that for the overall self-concept variable the overweight and obese groups were within the average recommended by the instrument; however, the lowest scores were observed in obese boys and girls. On the basis of specific predictors (BMI, age, SES and skin color), obese boys were significantly more likely to present imbalance in the Behavioral Adjustment and Freedom From Anxiety domains (2.6 and 3.1 times, respectively) than the normal weight group, irrespective of age, SES and skin color. For girls, the obese group was 2.0 to 2.7 times more likely to present imbalance in the TOT and Intellectual Status, Popularity and Happiness domains than the normal weight group, irrespective of age, SES and skin color. The results demonstrated a negative impact of overweight and obesity on the perception of overall self-concept and its domains.